(untitled) (UNED Research Journal, 2016)
The RAMSAR Site, Chaco wetlands, covers the eastern fringe of the Chaco province, with a surface of 508 000 ha and several environmental unit, like gallery forest, floodplain forests, palm savannahs, grasslands, and others. The studies about the spider fauna from its site are scarce. This study compares spider communities from forest and grassland in San Francisco ranch (27º30’26’’ S - 59º05’03’’ W) located in San Fernando Department and San Carlos ranch (26º57’’46’’ S - 58º38’12’’ W) located in Bermejo Department; on October and November 2013. The forest structure is different, San Francisco forest is mixed with Chaco vegetation and the cattle activity has destroyed an important part of it. The San Carlos forest is a forest gallery also constituted by paranaense species, with cattle activity too, but it with more control and carefulness by their owners. The spiders were collected by foliage beating, leaf litter sifting, hand collecting and G-vac (vacuum sampling) sampling methods. A total of 1 477 spiders grouped into 261 species/morphospecies from 34 families of Araneomorphae. Eighteen species are new records for Argentina. Araneidae was the most abundant families. Araneidae, Theridiidae and Salticidae were the most richness families. Species accumulation curves with 95% confidence interval show that there was significant difference only for grasslands. Rank abundance curve showed that community structure were different on both sites, referring to abundance, dominant species, species composition and proportion of rare species. The comparison of true diversity showed that San Carlos grassland and forest were more diverse than San Francisco, ones it could be related to vegetation structure and high degree of conservation. This study showed an important richness and abundance of spiders that integrate different communities on RAMSAR site areas, and suggests future research on others environments on this site.